Novel method for microencapsulation of eutectic hydrated salt as a phase change material for thermal energy storage. (19th April 2022) - Huo, Xianliang; Xie, Donghuan; Zhao, Zimo; Wang, Shujun; Meng, Fanbin
ABSTRACT: Inorganic hydrated salts have many advantages over organic phase change materials (PCMs), such as higher thermal storage density, low cost, non-toxicity and non-flammability. In this research, microcapsules loaded with eutectic hydrated salt (EHS) as the core material was fabricated via coacervation method at room temperature, with ethyl cellulose/acrylonitrile butadiene styrene as the shell material. EHS consisted of sodium sulfate decahydrate and disodium hydrogen phosphate dodecahydrate with a mass ratio of 1:3 was prepared as the PCM with its phase change temperature of 29.3°C and phase change enthalpy of 218.58 J/g. The chemical structures and morphology were investigated by Fourier transform infrared spectroscopy and scanning electron microscope. Results indicates that the almost spherical microcapsules, with diameter around 60 μm, are of core–shell microstructures and good chemical compatibility of the core and shell material. Differential scanning calorimetry results shows that microcapsules possess a high latent heat (178.36 J/g) and excellent thermal stability and reliability, which are suitable for thermal energy storage and management in practical applications. More importantly, the simple and environmentally conscious way of this study may be extended to other promising inorganics@organics PCMs with different core–shell structured compositions.